Married Women in The Labour Market: A Singapore Perspective - Cheong, Wai Min (2009)
Singapore’s economic development has been progressing rapidly over the past few decades. The level of education and intellectual capacity of her has been improving over the years. More women are having higher educational qualifications and assume senior positions in their careers. Like other developed countries, this success also brings along a unique set of social problems. The country has been having a dry spell in terms of fertility rates. In addition, a growing trend in delaying marriage and a decline of married women’s participation in the workforce after childbirth.